Pembangunan Infrastruktur dalam Islam: Tinjauan Ekonomi dan Sosial - Rifyal Zuhdi Gultom; Annisa Qadarusman Tini (ITB AAS INDONESIA Surakarta, 2020)
One strategy in achieving the desired goals of a country is through economic development. Indicators such as economic growth, income per capita population, unemployment, poverty, and others become a benchmark for the success of a country's economic development. One of the supporting facilities for a country's economic development is the development of infrastructure. Infrastructure itself is a driver of economic development in a country. One of the problems that is very important to be considered by a country or region is infrastructure problems that will have an impact on the sustainability of the region's economic development. In addition, infrastructure development must be in accordance with Islamic principles. Because Islam also pays attention to the problem of economic development, but still places it on the larger development problem, namely human development. The main function of Islam is to guide people in the right and right direction. All aspects related to economic development must be integrated with the development of humanity as a whole both economic and social aspects of concern